A Modified Pre-plating Method for High-Yield and High-Purity Muscle Stem Cell Isolation From Human/Mouse Skeletal Muscle Tissues - Yoshioka, Kiyoshi; Kitajima, Yasuo; Okazaki, Narihiro; Chiba, Ko; Yonekura, Akihiko; Ono, Yusuke (Frontiers in Cell and Developmental Biology, 2020)
Primary culture of skeletal muscle stem cells (MuSCs) is indispensable to study the dynamics of muscle regeneration and homeostasis. Here we describe the modified pre-plating method for isolating MuSCs in culture with greatly improved purity, yield, and procedure time. The protocol is based on the distinct adhesion characteristics of MuSCs. We reduced the procedure time to 2.5 days to obtain highly purified MuSCs through a newly employed re-plating step, which repeats incubation and cell-suspension. The re-plating step efficiently traps remaining fibroblastic cells, but not MuSCs, on a collagen-coated dish. Additionally, we confirmed that MuSCs can be isolated from small amounts of human/mouse muscle tissues, enabling us to perform experiments with amount-limited specimens. Thus, our method can be performed with basic laboratory equipment suitable for most facilities and without sophisticated MuSC handling techniques.